Long-term Efficacy of Botulinum Neurotoxin-A Treatment for Essential Blepharospasm - Lee, Seunghyun (Korean J Ophthalmol, 2018)
PURPOSE: In the present study, we investigated the treatment efficacy and clinical outcomes of botulinum neurotoxin-A (BoNT-A) administered for longer than 5 years to patients with essential blepharospasm. METHODS: We retrospectively reviewed 19 patients (male : female = 8 : 11) diagnosed with essential blepharospasm between March 2006 and July 2016 who underwent BoNT-A injections for over 5 years and were followed. Efficacy of 297 injections of Botox (n = 162), Meditoxin (n = 75), Hugel-tox (n = 40), or Dysport (n = 20) was based on the symptom improvement score at the final injection (−1, worse; 0, same; 1, better). Injection dose (botox unit), duration of efficacy (months), and adverse events were also investigated. RESULTS: Based on product type, significant differences in patient age (59.3 ± 9.8 years), disease period (5.0 ± 5.4 years), number of botulinum neurotoxin injections before visiting our clinic (1.6 ± 2.6), and follow-up period (7.2 ± 1.6 years) were not observed. Treatment efficacy score and injection dose of repetitive injections were 0.1 ± 0.5 and 39.1 ± 4.0 units, respectively, and did not show significant differences with repeated injections. Duration of response was 5.9 ± 5.4 months, but this significantly decreased as the injections were repeated (p < 0.01). Among the 297 injections, adverse events occurred 12 times (4.0%) with no severe sequelae. CONCLUSIONS: In this study, we showed that repetitive, long-term BoNT-A injections are considered a stable and effective treatment for essential blepharospasm in terms of consistent injection dose and maintenance of treatment efficacy. However, the duration of long-term efficacy could be decreased in patients injected repetitively.